The influence of age, ethnicity and body anthropometry on the level of serum osteocalcin and terminal-c telopeptides of type I collagen in men - Ima Nirwana Soelaiman,; Kok, Yong Chin; Isa Naina Mohamed,; Wan Zurinah Wan Ngah, (penerbit ukm, 2014)
Bone turnover markers (BTMs) are useful in the assessment of bone health status. However, the infl uence of age, ethnicity and body anthropometry on the level of BTMs in men remains understudied. This study aimed to determine the influence of these factors on the level of BTM, namely osteoclacin (OC) and C-terminal telopeptides of type 1 collagen (CTX-1) among Malay and Chinese men (N = 407) aged 20 years and above in Klang Valley. The subjects were recruited using purposive sampling method. Their height, body weight and body mass index were measured. Their blood was collected in the morning for serum OC and CTX-1 analysis using enzyme-linked immunoasorbent assays. Results showed that OC and CTX-1 levels were significantly higher in Malay compared to Chinese men (p < 0.05). Highest levels of OC and CTX-1 were observed in men aged 20-29 years, while the lowest levels were found among men aged 30-39 years (p < 0.005). No significant diff erences in the levels of both markers were found between the older men and those aged 30-39 years (p > 0.005). There were significant and negative correlations between OC and body mass index and weight, which were significant for men aged 20-39 years only (p < 0.05). Body anthropometry was not correlated with CTX-1 level in men (p > 0.05). As a conclusion, levels of BTMs in Malaysian men could be infl uenced by age, ethnicity and body anthropometry. Thus, these factors should be taken into consideration in the evaluation of bone health status of men using BTMs.